Choanalatresie - Sommerburg, Olaf; Plinkert, Peter K.; Baumann, Ingo (Monatsschrift Kinderheilkunde, 2019)
Choanal atresia (CA) is a rare malformation. Newborns with bilateral CA require rapid intubation and ventilation after birth as well as surgical recanalization as soon as possible. Unilateral CA leads to practically no respiratory complaints, becomes symptomatic later and therefore needs no immediate correction. Initial diagnostic exploration should be performed using a thin flexible endoscope. For final diagnosis surgical planning and exclusion of further craniofacial malformations, computed tomographic imaging is required. Surgical treatment currently focuses on transnasal endoscopy. For the success of surgery it is important to resect those parts of the vomer that are included in the atresia. The postoperative treatment includes the use of nasal sprays containing corticosteroids and nasal saline rinsing for several weeks. The rarity of the diagnosis impedes prospective randomized controlled studies, which enable a valid statement on the preferable surgical technique.